Headache Medicine: updates and bibliometric analysis - Andrade, Juliana Ramos de; Peres, Mario Fernando Pietro; Silva-Néto, Raimundo Pereira; Valença, Marcelo Moraes (Headache Medicine, 2022)
Introduction Headache Medicine is the official scientific journal of the Brazilian Headache Society that has been publishing clinical and experimental, qualitative, and quantitative research on headaches and orofacial pain for 28 years, as well as aspects related to pain that may have implications for headaches. In constant updating, Headache Medicine demonstrates commitment and scientific ethics following the international criteria for publication in the medical field. Objective Describe updates made in 2020 to the management and editorial process and bibliometric data from Headache Medicine publications and accesses to demonstrate their impact on headache science. Methods Data on the quantity and location of accesses until September 2022 were obtained from Google Analytics. The most accessed and read articles (originals, reviews, or case reports) were identified through the statistical reports of the Open Journal Systems (OJS). The journal's H5 index and the citations of each published paper were consulted in Publish or Perish and Google Scholar, respectively. Results In 2020, Headache Medicine obtained ISSN online, migrated its management to OJS, registered a Digital Object Identifier (DOI) on all articles published, linked the authors' ORCiD to the publication, and updated the publication of the numbers of each issue. Google Analytics has been monitoring Headache Medicine for just 2 years and has already accounted for more than 38,000 accesses from 150 countries. Brazil (29,282 accesses), the United States (2,186 accesses), Portugal (1,434 accesses) and China (377 accesses) are the 4 countries with the most access. Headache Medicine has published 202 original articles, reviews or case reports since 2010. The three most accessed articles with abstract and full article are literature review: Topiramate and cognitive function: review (Santos et al., 2005) with 1,152 accesses, Pizotifen for the treatment of migraine. (To see the complet abstract, please, check out the PDF.)